The Effect of Occupational Stress on the Quality of Life of Pharmacists in Saudi Arabia - Almogbel Y (Dove Medical Press, 2021)
Yasser Almogbel Department of Pharmacy Practice, College of Pharmacy, Qassim University, Buraidah, 51452, Qassim, Saudi ArabiaCorrespondence: Yasser AlmogbelDepartment of Pharmacy Practice, College of Pharmacy, Qassim University, Buraidah, 51452, Qassim, Saudi ArabiaTel +966 16 3014601Email y.almogbel@qu.edu.saPurpose: The job of a pharmacist is extremely demanding, and pharmacists play a vital role in improving the success of patients’ treatment plans and disease management outcomes. The objective of this study was to evaluate the association between pharmacists’ quality of life (QOL) and occupational stress in Saudi Arabia.Methods: This was a prospective, paper-based, cross-sectional survey. The World Health Organization Quality of Life – Brief scale (WHOQOL-BREF) was used to evaluate quality of life, and the Effort-Reward Imbalance (ERI) scale was used to assess occupational stress. The two scales were administered to licensed pharmacists working in Saudi Arabia, and demographic data were collected. Descriptive and analytical statistical tests were performed. Multiple linear regression was conducted to evaluate the association between work stress and QOL.Results: A total of 371 questionnaires were distributed, and 284 questionnaires were returned. The average age of the participants was 33.4 ± 6.5 years. Most were male (61.2%), married (62.9%), and had children (51.1%). Multiple linear regression analysis showed significant negative relationships between stress (β = -0.454; 95% CI, − 0.697 to − 0.211) and QOL, and between the presence of chronic diseases (β =  3.779; 95% CI, 0.597 to 6.961) and QOL, when holding other variables constant. Also, a positive association between male sex (β =  3.779; 95% CI, 0.597 to 6.961) and QOL was reported, when other variables were kept constant.Conclusion: Occupational stress and the presence of chronic diseases were found to have a negative influence on pharmacists’ QOL, while the male sex was associated with a better QOL. Moreover, QOL was linked to performance. Pharmacists are intensely involved in medication safety (use and administration), which might impact patients (at the micro-level) and the healthcare system (at the macro-level). Therefore, stress control is crucial to improve pharmacists’ QOL and performance in relation to patient health.Keywords: pharmacy profession, well-being, work climate, distress